Double burden of malnutrition among under-5 children in Garo ethnic community of Bangladesh: Prevalence and determinants - M. M. Mehedi Hasan; Nayeem Rahman; Farzana Afroz; Md. Nazrul Islam; Md. Serajus Saberin; Md. Tohin Hossain Somon; Md Reaz Ul Islam (Global Pediatrics, 2025)
Background: Malnutrition, especially in children, continues to be a serious public health concern worldwide. This study investigates the prevalence and risk factors of the double burden of malnutrition—undernutrition and overnutrition—among Garo under-five children in Sherpur, Bangladesh, where they reside most. Methods: A community-based cross-sectional study was conducted from January to April 2024, involving 336 Garo children aged 6 to 59 months. Data were collected through structured interviews with mothers and anthropometric measurements of children. Descriptive statistics, bivariate and multivariable logistic regression analyses were performed to assess associations between malnutrition indicators and sociodemographic factors. Results: Stunting (27.98 %) was the most prevalent form of malnutrition, followed by underweight (7.74 %), wasting (4.46 %), and overweight (7.74 %). Male children had significantly higher odds of stunting (AOR = 1.80, p = 0.032), and children from households with lower food expenditures (<500 BDT per day) were at greater risk of stunting (AOR = 4.03, p = 0.016). The odds of being overweight were 8.91 times greater for older children (48–59 months) (p = 0.005), which indicated a significant association. Conclusions: The study highlights the coexistence of undernutrition and overnutrition among Garo children, emphasizing the urgent need for targeted interventions. Addressing the double burden of malnutrition through culturally tailored programs and policy interventions is essential to improving child health in ethnic communities.